Edukasi Moderasi Beragama Melalui Seni dan Budaya Islam - Hasan, Moch. Sya'roni; Ma'arif, Muhammad Anas; Ainiyah, Qurrotul; Rofiq, Ainur; Mujahidin, Mujahidin (Lembaga Penelitian, Penerbitan dan pengabdian kepada masyarakat (LP3M) STIT Al-Urwatul Wutsqo Jombang., 2024)
The educational program for religious moderation through Islamic arts and culture for Generation Z at MI Bahrul Ulum Gedongboyo, Turi, Lamongan aims to instill moderate, inclusive and tolerant Islamic values. Adopting a participatory action research (PAR) approach, this program integrates the concept of religious moderation into the curriculum through Islamic arts and culture. Implementation includes the development of learning modules, extracurricular activities, and integration into regular subjects. Results show a significant increase in students' understanding of religious moderation, positive changes in attitudes towards diversity, and the ability to express moderate Islamic values ??through works of art. Key challenges include the diversity of student backgrounds and limited resources. The success of the program opens up opportunities for development and replication in other Islamic educational institutions. A holistic approach that integrates cognitive, affective and psychomotor aspects is the key to success. This program makes a significant contribution in forming a young generation of moderate and tolerant Muslims, as well as offering an innovative model in religious education to face the challenges of radicalism and intolerance